Dynamics of the Agricultural Sector and Food Security in the Border Areas East Nusa Tenggara Province – Timor Leste - Nalle, Frederic Winston; Kadir, Rifadli D.; Masniadi, Rudi (EKO-REGIONAL, 2024)
East Nusa Tenggara (NTT) Province is a strategic area bordering Timor-Leste, with significant potential in agriculture and trade. However, NTT faces food insecurity issues, reflected in high poverty rates and malnutrition prevalence, making it the province with the highest malnutrition rate in Indonesia. This study uses Multiple Linear Regression Method to analyze the impact of climate change, accessibility, education, agricultural diversification programs, and community participation on food security. A sample of 150 farmers from Kupang, South Central Timor, North Central Timor, Belu, and Malaka districts was randomly selected. The results show that these five variables significantly affect food security in NTT, both partially and simultaneously. Strategic recommendations include adopting climate change adaptation programs, improving accessibility, education, agricultural diversification, and strengthening community participation in decision-making processes.